Natural compounds regulating fatty acid oxidation in the treatment of diabetic kidney disease - Sun, Jianing; Yin, Chengqian; Li, Zhe; Gao, Xiangyu; Li, Songlin; Gao, Hua; An, Yan; Liu, Peng; Liu, Na (Frontiers in Nutrition, 2025)
Diabetic kidney disease (DKD) is one of the leading causes of end-stage renal disease worldwide, and lipid metabolism disorder is a key factor in accelerating its progression. Among them, the impaired fatty acid oxidation (FAO) function of renal tissue constitutes one of the core pathological links of lipid metabolism disorders. In DKD, impaired FAO function can directly lead to lipid accumulation, mitochondrial stress, and trigger an inflammatory cascade, thereby promoting the occurrence and development of glomerulosclerosis and renal tubular injury. However, the efficacy of current DKD treatment strategies is still limited. Natural compounds (such as polyphenols, phenolic acids, alkaloids, glycosides, and carotenoids) have shown potential in renal protection due to their multi-target and multi-pathway characteristics. Studies have shown that regulating the FAO process in the context of lipid metabolism disorders is a crucial mechanism by which natural compounds can exert anti-DKD effects. It is worth noting that peroxisome proliferator-activated receptors (PPARs) are core transcription factors that regulate FAO. Specifically, these active ingredients can upregulate the expression of their downstream target genes by activating the PPAR signaling pathway (especially PPARα), thereby improving FAO function, correcting abnormal lipid metabolism, and ultimately delaying the progression of renal pathological mechanisms such as inflammation and fibrosis. The above findings provide an essential scientific basis for the development of new, safe, and effective DKD therapeutic drugs.